Economics of Cage Culture of Fish in Karnataka - Patil, Kiran Kumar R; B. Chinnappa; K. C. Shashidhara; H. S. Sowmya (Fishery Technology, 2022)
Cage culture has emerged as a suitable alternative to fishermen to sustain their livelihood. Cage culture is extensively practiced in Karnataka. The present study aimed at assessment of economics of cage culture in Udupi district of Karnataka. Cage culturing of sea bass and red snapper in two small cages (2S), one small and one large cage (S+L) and two small and one large cage (2S+L) was observedin the study area. The capital investment was highest in case of 2S+L at Rs. 1,34,380. The total costincurred on production of sea bass and red snapper came to Rs. 4,38,885 and Rs. 8,11,939.20 in case ofS+L and 2S+L, respectively. Fishermen following 2S+L was found to be economically successful in terms of net returns (Rs. 233.37/kg and Rs. 122.94/ kg) compared to S+L (Rs. 226.45/kg and Rs. 78.14/ kg) in cage culture of sea bass and red snapper due to the operation of scale economies. The cage system2S+L was found economically viable but was fraught with constraints in operational and financial management.